Lectura Dantis : Purgatorio - Mandelbaum, Allen, 1926-2011; Oldcorn, Anthony; Ross, Charles (Joan Palevsky imprint in classical literature., 2008)
Contains commentary on the Purgatorio by various scholars. This book presents to the nonspecialist reader one of the cantos of the transitional middle cantica of Dante's unique Christian epic. It provides awareness of Dante's timeless aspirations and achievements.